2018
DOI: 10.1002/dev.21614
|View full text |Cite
|
Sign up to set email alerts
|

Learning of hierarchical serial patterns emerges in infancy

Abstract: Recursive, hierarchically organized serial patterns provide the underlying structure in many cognitive and motor domains including speech, language, music, social interaction, and motor action. We investigated whether learning of hierarchical patterns emerges in infancy by habituating 204 infants to different hierarchical serial patterns and then testing for discrimination and generalization of such patterns. Results indicated that 8- to 10-month-old and 12- to 14-month-old infants exhibited sensitivity to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…We examined this question using a modified version of an A‐not‐B task, in which a change in the hiding event sequence was paired with a change in the experimenter hiding the toy. We tested 9‐month‐old infants, an age‐group who are both capable of organizing simple audiovisual inputs into predictable rule structures (Werchan et al., 2015; Werchan et al, 2016; Lewkowicz et al., 2018) and who consistently show the A‐not‐B error (Diamond, 2002). We found that infants’ search behavior was consistent with using the identity of the experimenter to organize events into S‐A‐O rules that guide subsequent action (see Table 4 for a summary of manipulations and findings).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We examined this question using a modified version of an A‐not‐B task, in which a change in the hiding event sequence was paired with a change in the experimenter hiding the toy. We tested 9‐month‐old infants, an age‐group who are both capable of organizing simple audiovisual inputs into predictable rule structures (Werchan et al., 2015; Werchan et al, 2016; Lewkowicz et al., 2018) and who consistently show the A‐not‐B error (Diamond, 2002). We found that infants’ search behavior was consistent with using the identity of the experimenter to organize events into S‐A‐O rules that guide subsequent action (see Table 4 for a summary of manipulations and findings).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, higher‐order contexts can be used to cue lower‐order rules (S‐A‐O associations) that are most appropriate for a given context, thereby reducing complexity of learning problems. Prior research reveals that infants as young as 8 months of age can organize audiovisual inputs into predictable rules or sequences of this sort during incidental learning, even in environments where there is no immediate or obvious benefit to doing so (Lewkowicz, Schmuckler, & Mangalindan, 2018; Werchan, Collins, Frank, & Amso, 2015; Werchan & Amso, 2020). Other data show that infants can use social information, in the form of face‐voice contexts, to organize different sets of spoken labels for the same objects (Werchan et al., 2015; Werchan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other recent evidence indicates that chunking may also occur as a perceptual process (Gilbert et al 2014(Gilbert et al , 2015. Recent developmental research has demonstrated chunking abilities in human infants (Lewkowicz et al 2018).…”
Section: Introductionmentioning
confidence: 99%